The weevil Dynamis borassi (Coleoptera: Curculionidae: Dryophthorinae) associated with native palms in forests and disturbed areas in Buenaventura, Colombia. (2020)
Deforestation produces homogeneous agricultural environments creating an imbalance between herbivores and their hosts. Since 2010, there has been a phytosanitary crisis in the peach palm (or chontaduro), Bactris gasipaes in the Colombian Pacific Region which can be attributed to two species of palm weevils: Rhynchophorus palmarum and Dynamis borassi. It has been proposed that deforestation of native palms, used by these weevils, induces these to find new resources in the peach palm. This study examined the association of these two weevils with native palms near chontaduro crops and how this occurs in two types of habitats. Six secondary forests and six anthropogenically disturbed areas were visited in third administrative division: “corregimientos” 1 and 2 (Zone A) and 7 and 8 (Zone B) in the municipality of Buenaventura. Three 50 x 100 m plots were designated in each zone, all palms with damage being recorded; the sampling was also complemented with a free sample. Twelve palm species distributed into one subfamily and nine genera were identified. A total of 271 unopened inflorescences were examined in Zone A and 501 in Zone B. Only evidence of damage was found in individuals of the “milpesos” palm (Oenocarpus bataua), an economically exploitable species. The proportion of palms affected in terms of habitat was significantly higher in the disturbed habitat. This is the first record that quantifies a high percentage of association between D. borassi and the “milpesos” palm in the Colombian Pacific Region, a phenomenon that could be explained by agroecological hypotheses.